Stategraphy : toward a relational anthropology of the state - Thelen, Tatjana; Vetters, Larissa; Benda-Beckmann, Keebet von (Studies in social analysis, 2018)
Stategraphy-the ethnographic exploration of relational modes, boundaries, and forms of embeddedness of state actors-offers crucial analytical avenues for researching state transformations. By exploring interactions and negotiations of local actors in different institutional settings, the contributors explore state transformations in relation to social security in a variety of locations spanning from Russia, Eastern Europe, and the Balkans to the United Kingdom and France. Fusing grounded empirical studies with rigorous theorizing, the volume provides new perspectives to broader related debates in social research and political analysis.